The molecular basis of force selectivity by PIEZO2 - Eric M. Mulhall; Oleg Yarishkin; Rose Z. Hill; Anna K. Koster; Ardem Patapoutian (Nature, 2026)
Abstract PIEZOs are mechanically gated ion channels that transduce force into electrochemical signals 1 . PIEZO1 responds to diverse stimuli including membrane stretch 2 and shear stress 3 , whereas PIEZO2 is generally tuned to detect cellular indentation 4,5 . The functional specialization of PIEZO2 is proposed to underlie its distinct physiological roles, including mediating the sense of touch 6,7 . How PIEZO2 achieves this selectivity despite its close structural similarity to PIEZO1 is unclear. Here we combine single-molecule MINFLUX fluorescence nanoscopy with electrophysiology to link the conformational states of PIEZO2 to channel gating in intact cells. We find that PIEZO2 is intrinsically more rigid than PIEZO1, and that disparate mechanical stimuli paradoxically evoke opposite conformational and gating responses in each channel. These unique gating properties arise in part from a connection to the actin cytoskeleton, and we identify filamin-B (FLNB) as a molecular tether that is required for this interaction. This complex alters how force is transmitted to PIEZO2 and confers heightened sensitivity to and selectivity for cellular indentation. PIEZO2 and FLNB are co-expressed in somatosensory neurons and colocalize within tens of nanometres at the end organs of cutaneous mechanosensory afferents. These findings help to explain why PIEZO2 is a specialized mechanosensor and provide a molecular blueprint for understanding how cells decode diverse mechanical stimuli across tissues and organ systems.